2014
DOI: 10.3399/bjgp14x677518
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in older women with pelvic floor symptoms: a cross-sectional study in general practice

Abstract: BackgroundPelvic floor symptoms are common and are negatively associated with sexual function which, in turn, is an important aspect of quality of life. The majority of older women with pelvic floor symptoms are treated in general practice but evidence from studies in general practice on the sexual functioning of these women is scarce. AimThis study examined predictors of sexual inactivity in older women with pelvic floor symptoms in general practice and of sexual functioning in those women who are sexually ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
1
11
1
2
Order By: Relevance
“…Changes in sexual function cannot be evaluated independently of changes in pelvic floor symptoms as it is well known that bowel/bladder symptoms impair sexual function [24,25]. A Cochrane review of prolapse repair found improved pelvic floor symptoms in 14 trials that used validated pelvic floor questionnaires [26].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in sexual function cannot be evaluated independently of changes in pelvic floor symptoms as it is well known that bowel/bladder symptoms impair sexual function [24,25]. A Cochrane review of prolapse repair found improved pelvic floor symptoms in 14 trials that used validated pelvic floor questionnaires [26].…”
Section: Discussionmentioning
confidence: 99%
“…Panman et al [10] found that increasing age and a lower educational level were predictors of sexual inactivity, whereas pelvic floor symptoms and prolapse were not. In contrast, most women in both of our groups enjoyed better sexual functioning after VH to treat POP.…”
Section: Discussionmentioning
confidence: 99%
“…A strong pelvic floor is associated with higher rates of sexual activity as well as higher sexual function scores [31]. In sexually active women, poorer sexual functioning was associated with more symptom distress and with pelvic floor surgery [32].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%